2016
DOI: 10.1039/c6ra11041j
|View full text |Cite
|
Sign up to set email alerts
|

Novel synthesised flavone derivatives provide significant insight into the structural features required for enhanced anti-proliferative activity

Abstract: Synthesis and antiproliferative evaluation of a library of 76 methoxy and hydroxy flavones, and their 4-thio analogues showed that the novel thioflavones 15f and 16f exhibit 7–46 fold greater anti-proliferative potency than the natural flavone chrysin (2d).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 63 publications
0
43
0
Order By: Relevance
“…Exhaustive O -methylation of quercetin to the 3,3′,4′,5,7- O -pentamethyl derivative ( 20 , Figure 4 ) followed by thionation gave access to compound 54 , which was eventually deprotected yielding 53 [ 55 , 56 ]. It has been shown that both compounds possess in vitro antiangiogenic and antiproliferative properties [ 55 ].…”
Section: Synthesis and Anticancer-related Activities Of Quercetin mentioning
confidence: 99%
See 2 more Smart Citations
“…Exhaustive O -methylation of quercetin to the 3,3′,4′,5,7- O -pentamethyl derivative ( 20 , Figure 4 ) followed by thionation gave access to compound 54 , which was eventually deprotected yielding 53 [ 55 , 56 ]. It has been shown that both compounds possess in vitro antiangiogenic and antiproliferative properties [ 55 ].…”
Section: Synthesis and Anticancer-related Activities Of Quercetin mentioning
confidence: 99%
“…Overall, derivative 20 was found to be the top of the line as it optimally balanced the high antiangiogenic activity with minimal toxicity. Further antiproliferative studies using breast cancer cell line MDA-MB-231 evidenced that the 4-thio compounds, and in particular 53 , had greater effects than 20 and the parent quercetin [ 56 ]. However, 53 did not reach the IC 50 at 10 μM.…”
Section: Synthesis and Anticancer-related Activities Of Quercetin mentioning
confidence: 99%
See 1 more Smart Citation
“…The synthetic flavones used in this study are grouped into four main classes namely; hydroxy flavones with free –OH and 4-C=O, hydroxy 4-thioflavones with free –OH and 4-C=S, methoxy flavones with –OMe and 4-C=O and methoxy 4-thioflavones with–OMe and 4-C=S 35 . The hydroxy flavones include 7,8-dihydroxy-2-phenyl-4 H -chromen-4-one (F-1), 7,8-dihydroxy-2(thiophen-2-yl)-4 H -chromen-4-one (F-2), 2-(furan-2-yl)-7-8,dihydroxy-4 H -chromen-4-one (F-3) and 7,8-dihydroxy-2(pyridine-3yl)-4 H -chromen-4-one (F-4).…”
Section: Methodsmentioning
confidence: 99%
“…Further, studies focusing on the blood-brain barrier (BBB) permeability of flavonoids have highlighted that the lipophilic flavonoids possess greater BBB permeability than the polar flavonoids 22,23 ; the permeability potency of the compounds also correlated with their lipophilicity (log P) [24][25][26] . With our interest in developing novel flavone derivatives as therapeutic agents, we had previously synthesised and characterised a library of 76 hydroxy flavones, methoxy flavones and their 4-thio derivatives 27 (Figure- (Figure-1). The purities of all compounds were established prior to evaluation, by reverse phase HPLC, and were found to be >95%.…”
Section: A R T I C L E I N F O Abstract 1 Introductionmentioning
confidence: 99%